Analisis Pengaruh Konflik Keluarga dan Pekerjaan Terhadap Kepuasan Kerja pada Dosen di Perguruan Tinggi Swasta di Kota Prabumulih, Sumatera Selatan - Maiza Fikri (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
Conflicts of interest between family and work there in general is often experienced due to work properly guided so that job satisfaction can be created with good. Factors that affect the family-work conflict terhadapan satisfaction that type of work, work location, behavioral couples, and salary. The design of this study is descriptive quantitative research with taking three object in Colleges precisely on the other side of Palembang city namely the STMIK YPP Prabumulih, STIE YPP Prabumulih and STIE AL-Furqon. Methods of data collection using questionnaires, the number of respondents is 75 and using incidental sampling technique. This study aims to find out there is a family-work conflicts influence on job satisfaction at the faculty. Didgunakan analysis is simple regression analysis, analysis of correlation coefficients and coefficients of determination. By using simple regression can be concluded that the family-work conflict there is significant influence on job satisfaction with a P value of 0.000 ˂ value of 0.05, whereas the correlation analysis of the results obtained Person bivariate correlation between conflict and satisfaction is -0.421 which means there is no way the relationship between variable work-family conflict and job satisfaction variables, while the value of sig (2-tailed) obtained 0,000, which means a significant ˂ 0.05 then there were significant correlations (Ha accepted).